A Need for Paradigm Shift to Improve Supply Chain Management of Fruits & Vegetables in India - Halder, Piali; Pati , Simayan (Asian Journal of Agriculture and Rural Development, 2011)
As the Indian population is increasing, the demand for fresh fruits and vegetables is also increasing. Owing to the perishable nature and very short shelf life, these items require proper storage and transportation facilities in order to reach to the customer in fresh state. A lack of investment in agriculture makes the country vulnerable to international price shocks as well as exchange-rate volatility. The present study undertakes a thorough review of basic and contemporary literature available and tries to explain the challenges & opportunities in supply chain management to create a bridge between rural & urban market. It also brings out relevant research gaps and overlooked problems in the supply chain. The proposed research work is exploratory in nature using secondary sources.